PENGARUH KINERJA AIR TRAFFIC CONTROLLER TERHADAP WAKTU TUNDA PADA TAXIWAY (TAXI-OUT DELAY) DI BANDAR UDARA INTERNASIONAL SOEKARNO – HATTA TANGERANG BANTEN - Huriyah Fitr; Rany Adiliawijaya P; Yudha Abimanyu (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
This research aims to get an idea of whether there are impact between air traffic controller performances with taxi out delay in Soekarno – Hatta International Airport Tangerang Banten. The method used is quantitative research method. It can be inferred from the research that there was a negative relationship between air traffic controller performance with taxi out delay as big as 0,831. A negative correlation indicates that the better the performance of air traffic controller, the fewer aircraft is affected by delay at departure. Determination coefficient is at 70%, which means that the impact of air traffic controller performance toward taxi out delay is 70% and the rest is determined by other factors not included in the research section. The equation obtained from the regression test is Y = 1932,396 – 26,561 X. So, if the ATC performance level rises by 1, then taxi out delay will decrease by 26,561 in the contant 1932,396, it is necessary to disseminate information to aerodrome control tower officers to improve and maintain performance, regularly evaluate aerodrome control tower performance, conduct training or refresh courses for ATC personnel, optimize flight time slot settings and implementing ground delay program to reduce delay.